The Portrait of Interreligious Harmony: A Phenomenon Study of Inter-Faith Family Harmony in Gunung Kidul, Yogyakarta - Muhammad Muhajir; Arif Al Anang (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2021)
This study aims to delve into the building harmony of interfaith families in Jetis, Hargomulyo, Gedangsari, Gunung Kidul Yogyakarta. It explores how the family ensures rights and obligations, educates children, provides freedom of worship and maintains relations with the family and the surrounding communities. In addition, it also explains how Islam views the harmony of families of interfaith couples. The results showed that the people of Jetis kampong attempted to fulfill their rights and obligations properly, such as the provision of proper livelihoods, not less and not excessive, although the level of fairness of each individual is different from one person to another. In terms of religion, the couples were able to carry out religious activities separately; they mutually support one another by creating tolerance in the family. Penelitian ini bertujuan untuk mendeskripsikan praktek pembentukan keluarga harmonis pasangan keluarga beda agama di Dusun Jetis, Hargomulyo, Gedangsari, Gunung Kidul Yogyakarta, yang meliputi bagaimana pemenuhan hak dan kewajiban, bagaimana pendidikan anak, bagaimana kebebasan beribadah dan bagaimana relasi dengan keluarga maupun masyarakat sekitar, serta menjelaskan bagaimana tinjauan Islam terhadap keharmonisan keluarga pasangan beda agama. Hasil penelitian menunjukkan bahwa masyarakat Dusun Jetis dalam praktek pembentukan keluarga harmonis dilihat dari segi pemenuhan hak dan kewajiban sudah terpenuhi dengan baik, serta dalam hal keagamaan keduanya mampu menjalankan aktivitas keagamaan secara terpisah namun saling mendukung antara satu dengan yang lainnya dengan memunculkan sikap toleransi dalam keluarga.